SEMANTIC PECULIARITIES OF SPORT PHRASEMES - Giyosjon Abdurakhmonov; Eshkoraev Esan (PEDAGOGS, 2024)
Abstract: – The article analyses the semantic features of phraseological units in sport. The purpose of the work is to study the phraseological units of a particular area of usage in sport. The objectives of the study are to identify thematic groups of phraseological units and defining their pragmatic goals in the genre of sports journalism as a kind of spontaneous public speech. Collected material can be used in linguistic and stylistic analysis of texts of various styles and genres. They are mainly considered to be the product of sport commentators’ intelligence. We also write about the importance of the context while translating phraseological units. He claims that depending on the context the translation of the same phraseological units may differ. The author also explains the differences between sport phrases and terms using various sport matches. We come to the conclusion that the above-mentioned methods are very important while translating phraseological units. The importance of phraseological units, namely sport phrases and terms in the communication process relating to sport terminology has been stated in the article as well.